Translational Universality: The Struggle over the Universal - Saša Hrnjez (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2020)
The aim of this paper is to investigate the idea of universality through the lens of translation, in an attempt to sketch out what can be called a translational universality. As the starting point, I will take into consideration the recent Étienne Balibar's works on the universals, and especially his strategy of translation, i.e. the strategy of enunciating the universal by means of translational process. In the next step, I will analyze political consequences of the universalizing practices of translation, which due to their capacity to enunciate the universals, according to Balibar's thesis, have generated political communities. In order to examine this aspect, I will discuss the constitutive role of translation in the formation (Bildung) of German cultural identity in the 19th Century, by exposing Humboldt-Schleirmacherian model of translation. In doing so I will lean on Berman's study on translation in Romantic Germany and on Venuti's political reading of nationalist narratives of typically German foreignizing translation. The conception of Bildung, envisaged as an experience of the otherness through translation, will be approached as a historical model to understand the notion of translational universality that is at issue in this paper. After these historical and philosophical analyses, which in translation view one possible way to articulate a certain struggle over the universal from the particular position of cultural difference, the article will address some questions regarding our contemporary situation: what would be a historically different and potentially emancipatory form of universality? What are the translational capacities of such a universality to generate a new framework for political communities?